2010
DOI: 10.1055/s-0028-1109957
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Prevalence and Risk Factors for Gallstone Disease in an Urban Population of Children and Adolescents

Abstract: Obesity appears to be a risk factor in the development of gallstones in childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Cholesterol stones, in fact, are becoming increasingly more common in children 169-171. In unselected pediatric populations, the prevalence rates are reported between 0.1% to 1.0% 170,172. One explanation for this increase is greater access to and use of abdominal ultrasonography in children 173.…”
Section: Gallstone Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol stones, in fact, are becoming increasingly more common in children 169-171. In unselected pediatric populations, the prevalence rates are reported between 0.1% to 1.0% 170,172. One explanation for this increase is greater access to and use of abdominal ultrasonography in children 173.…”
Section: Gallstone Diseasementioning
confidence: 99%
“…In obese children and adolescents, the prevalence may be as high as 2.0% 171. Other risk factors for gallstone disease in childhood include: female gender, pregnancy and oral contraceptive use; being of Mexican-American origin; drug exposure to cephalosporins, ceftriaxone or diuretics; a history of cardiac surgery or bowel resection, and having cystic fibrosis 149,172,173,176. In fact, the risk factors for pediatric gallbladder disease now more closely resemble those in adults.…”
Section: Gallstone Diseasementioning
confidence: 99%
“…Concomitant with the epidemic of childhood obesity [7, 8] and the shift towards extreme childhood obesity [7], the prevalence of gallstones in children and adolescents may be increasing due to childhood obesity. Results from small hospital-based studies suggest that obesity may be a risk factor for gallstones in adolescents [9, 10]. Cholecystectomy is also becoming more frequent in this age group [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a Canadian population-based, retrospective cohort, the crude incidence of cholecystectomy in subjects under 18 years of age increased from 8.8 per 100,000 person-years in 1993 to 13.0 per 100,000 person-years in 2012 8 , and a retrospective study in the US over a nine-year period ending in 2012 registered an increment of cholecystectomies due to pediatric non-hemolytic (cholesterol) gallstones of 216% 9 . It has been suggested that this epidemiologic increment during childhood could be due to the increasing prevalence of obesity 6 , 10 16 , physical inactivity, diabetes, and early pregnancy 6 .…”
Section: Introductionmentioning
confidence: 99%